Portfolio rebalancing and the transmission of large-scale asset programmes: Evidence from the euro area - Ugo Albertazzi; Miguel Boucinha; Bo Becker (European Central Bank (ECB), 2018)
Large-scale asset programmes aim to impact the real economy through the financial system. The ECB has focused much of its policies on safe assets. An intended channel of transmission of this type of programme is the "portfolio rebalancing channel", whereby investors are influenced to shift their investments away from such safe assets towards assets with higher expected returns, including lending to households and firms. We examine the portfolio rebalancing channel around the ECB's asset purchase program (APP). We exploit cross-sectional heterogeneity in the impact of APP on the valuation of the financial portfolio held by different sectors of the European economy. Overall, our results provide evidence of an active portfolio rebalancing channel. In more vulnerable countries, where macroeconomic unbalances and relatively high risk premia remain, APP was mostly reflected into a rebalancing towards riskier securities. In less vulnerable countries, where constraints on loan demand and supply are less significant, the rebalancing was observed mostly in terms of bank loans. Examining large European banks, we confirm similar geographical differences.
Keywords: E44; E51; G21; 330; quantitative easing; unconventional monetary policy; portfolio rebalancing; search for yield